2020
DOI: 10.1016/j.earlhumdev.2020.105161
|View full text |Cite
|
Sign up to set email alerts
|

Understanding COVID-19: A hypothesis regarding digit ratio (2D:4D), ACE I/D polymorphism, oxygen metabolism and national case fatality rates

Abstract: Objective Male digit ratio (2D:4D) correlates positively with the national case fatality rate (CFR) for COVID-19. The severity of COVID-19 may be influenced by a counterbalance between the angiotensin-converting enzyme (ACE) and angiotensin-converting enzyme 2 (ACE2). SARS-CoV2 cleaves with ACE2 and enters cells leaving an unopposed effect of ACE in the lungs. Both 2D:4D and the ACE I/D polymorphism are covariates of oxygen metabolism. COVID-19 leads to lung damage and a reduction in oxygen satura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…In short, according to the model of Manning and Fink (1), even a very small change in digit ratio should produce an implausibly large increase in mortality, which questions the credibility of their reported results. That these relationships hold over time unfortunately does not aid in their interpretation (2,3).…”
Section: Statistical Inferencementioning
confidence: 98%
See 2 more Smart Citations
“…In short, according to the model of Manning and Fink (1), even a very small change in digit ratio should produce an implausibly large increase in mortality, which questions the credibility of their reported results. That these relationships hold over time unfortunately does not aid in their interpretation (2,3).…”
Section: Statistical Inferencementioning
confidence: 98%
“…In a recent series of articles, Manning and Fink report the association of national-level index to ring finger ratio (2D:4D) with national case fatality rates (1)(2)(3), and test the associations of national-level ACE1 allele frequency and the ACE2 genotype on the same outcome (3). 2D:4D has long been thought to correlate negatively with prenatal androgen exposure, such that shorter index fingers relative to ring fingers indicate more prenatal androgen exposure (12).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the related data of each city is not available in China, so we cannot consider the effects of them in the model. Finally, the biological differences of residents among different cities can be taken into consideration in the future studies on determinants on the CFR with COVID-19 at the city level, including the effects of digit ratio (2D:4D) and ACE (Angiotensin-Converting Enzyme) I/D polymorphism on the CFR (55)(56)(57)(58).…”
Section: Data Availability Statementmentioning
confidence: 99%
“…A genetic deletion/insertion of a 285 bp Alu repeat sequence in intron 16 of the ACE gene fragment insertion (I allele) or its absence (D allele) is of particular importance. Insertion of the extra fragment (ACE I allele) is associated with lower ACE activity, whereas its absence (ACE D allele) leads to higher ACE activity (Woods et al, 2000;Manning and Fink, 2020) and angiotensin II levels (Sarangarajan et al, 2020). While the ACE I/D genotype modulates ACE2 expression and the ACE D allele is associated with the infection course and mortality due to COVID-19 (Delanghe et al, 2020;Yamamoto et al, 2020), an earlier study has shown that the ACE I/D and ACE D/D genotypes provide relative protection from cerebral malaria in an Indian cohort (Dhangadamajhi et al, 2010).…”
mentioning
confidence: 99%